2021
DOI: 10.3390/plants10050963
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Double-Stranded RNA Targeting 2b and CP Genes of Cucumber mosaic virus Protects Plants against Local and Systemic Viral Infection

Abstract: Cucumber mosaic virus (CMV) is a destructive plant virus with worldwide distribution and the broadest host range of any known plant virus, as well as a model plant virus for understanding plant–virus interactions. Since the discovery of RNA interference (RNAi) as a major antiviral defense, RNAi-based technologies have been developed for plant protection against viral diseases. In plants and animals, a key trigger of RNAi is double-stranded RNA (dsRNA) processed by Dicer and Dicer-like (DCL) family proteins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The exogenously applied dsRNAs entered not only fungal cells but also plant cells and plant vascular system. They were processed to siRNAs and initiated RNA silencing, supporting the conclusion that observed resistance is an RNAi-mediated process [ 11 , 16 ]. The exogenous dsRNAs and siRNAs have been shown to spread systemically from the treated leaves to non-treated ones [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The exogenously applied dsRNAs entered not only fungal cells but also plant cells and plant vascular system. They were processed to siRNAs and initiated RNA silencing, supporting the conclusion that observed resistance is an RNAi-mediated process [ 11 , 16 ]. The exogenous dsRNAs and siRNAs have been shown to spread systemically from the treated leaves to non-treated ones [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 59%
“…Recent studies increasingly demonstrate the ability of plants to uptake and process exogenous RNAs and the effectiveness of exogenous RNAs against plant pathogens and pests [ 9 , 44 , 46 ]. Recent studies reported on the substantial induction of plant viral [ 14 , 15 , 16 , 17 ], fungal [ 11 , 12 , 13 ], and insect [ 47 , 48 ] resistance after external application of dsRNAs, hpRNAs, and siRNAs targeting essential genes of the pathogens. The exogenously applied dsRNAs entered not only fungal cells but also plant cells and plant vascular system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that spraying plants with dsRNAs and siRNAs encoding key genes of plant pathogenic fungi [16][17][18][19][20][21] and viruses [22][23][24][25][26][27] effectively reduces development of the pathogens and suppresses the infection process. These externally applied dsR-NAs and siRNAs have been shown to spread systemically into plant tissues and were uptaken by the fungal cells inducing a RNAi-mediated silencing of the targeted genes of the pathogens [16,17,21,27].…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing number of studies that show induction of plant fungal [16][17][18][19][20][21] and viral [22][23][24][25][26][27] resistance after external application (spraying or mechanical inoculation) of dsRNAs, siRNAs, or hpRNAs designed to target virulence-related genes of the pathogens. Recent studies have also provided evidence that both plants and infecting pathogens were capable of the RNA uptake, and this eventually triggered RNAi-mediated silencing of the pathogen virulence-related genes [16,17,21,22,27].…”
Section: Introductionmentioning
confidence: 99%